The Relationship between Dietary Intake of Anti-Oxidant Micronutrients and the Rate of Recovery in Burn Patients - Adjepong, Mary (2014)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the award of Master of Philosophy Degree in Human Nutrition and Dietetics